Why Users Choose Mobile Banking: Behavioral Insights using UTAUT - Wati, Karyani Eka; Khuzaini , Khuzaini; Wijaya, Nur Qoudri (International Journal of Industrial Engineering, Technology & Operations Management, 2024)
Advances in digital technology within the banking sector have intensified competition among banks, prompting both government and private banks in Indonesia to adopt various strategies to enhance the quality and diversity of financial services offered to their customers. These strategies include developing internal digital banking systems focusing on multichannel delivery, particularly mobile banking. This research aims to test and analyze mobile banking users' behavioral intentions and behaviors by applying the Unified Theory of Acceptance and Use of Technology (UTAUT) model. The study employed a descriptive quantitative approach with data collected through purposive sampling. A questionnaire was distributed to 125 mobile banking users in Surabaya, of whom 100 responded. The findings reveal that performance expectancy, effort expectancy, and social influence positively and significantly influence the behavioural intention to use mobile banking. Behavioural intention, in turn, has a positive and significant impact on use behaviour. However, facilitating conditions have a positive but insignificant influence on the use behaviour of mobile banking users in Surabaya. This study provides valuable insights into the factors driving mobile banking adoption and usage in Indonesia. These findings can inform the development of more effective strategies to promote digital financial services.